2012
DOI: 10.1002/ibd.22944
|View full text |Cite
|
Sign up to set email alerts
|

Common NOD2 risk variants in African Americans with Crohnʼs disease are due exclusively to recent Caucasian admixture

Abstract: Background Crohn’s disease (CD) is highly heritable. NOD2 has emerged as the main susceptibility gene among individuals of European ancestry; however, NOD2 does not appear to contribute to CD susceptibility among many non-European populations. Today’s African American (AA) population represents an admixture of West African (80%) and European (20%) ancestry. Since genotype-based tools are becoming increasingly available for CD, it is important that we validate the risk variants in different populations, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…In contrast to prior reports, in which ASCAs were known to be associated with white populations, ileal involvement, and NOD2 status, the association between ASCA and complicated disease and disease requiring surgery is not the result of European admixture. 9, 32 Our findings do concur with prior literature regarding the association between anti-OmpC with complicated disease and the need for surgery in NE populations. 5, 33, 34 …”
Section: Discussionsupporting
confidence: 89%
“…In contrast to prior reports, in which ASCAs were known to be associated with white populations, ileal involvement, and NOD2 status, the association between ASCA and complicated disease and disease requiring surgery is not the result of European admixture. 9, 32 Our findings do concur with prior literature regarding the association between anti-OmpC with complicated disease and the need for surgery in NE populations. 5, 33, 34 …”
Section: Discussionsupporting
confidence: 89%
“…Some studies have shown that disease markers identified in European ancestry populations may also be observed in admixed populations. For example, the frameshift NOD2 risk variant found in European populations are also associated with CD in African Americans, albeit at much lower allele frequencies, consistent with the recent European admixture present in African Americans 41, 42 …”
Section: Population Differences In Ibdmentioning
confidence: 70%
“…For the meta-analysis of R702W, L1007fs and G908R, we included data from 89, 90 and 96 published articles(for R702W, G908 and L1007fs, respectively) with a combined total of 23,703 cases and 22,873 controls, which were published before December 31 st , 2016( D’Addabbo et al 2009 ; Schoultz et al 2009 ; Yazdanyar et al 2009 ; Csöngei et al 2010 ; Dassopoulos et al 2010 ; Gazouli et al 2010 ; Glas et al 2010 ; Hoffmann et al 2010 ; Lacher et al 2010 ; Sventoraityte et al 2010 ; Yazdanyar et al 2010 ; Naderi et al 2011 ; Adeyanju et al 2012 ; Azzam et al 2012 ; Hama et al 2012 ; Kanaan et al 2012 ; Akyuz et al 2013 ; Meddour et al 2014 ; Boukercha et al 2015 ; Salkic et al 2015 ), and conducted the analysis in R using the ‘meta’ package. We calculated the odds ratios for the three variants in the meta-analysis using DerSimonian-Laird statistics as a random-effects model.…”
Section: Methodsmentioning
confidence: 99%